Staff Experiences Forming and Sustaining Palliative Care Teams in Nursing Homes. (3rd January 2018) - Norton, Sally A; Ladwig, Susan; Caprio, Thomas V; Quill, Timothy E; Temkin-Greener, Helena
Abstract: Background and Objectives: Building palliative care (PC) capacity in nursing homes (NH) is a national priority and essential to providing high quality care for residents with advanced illness. We report on NH staff experiences in developing and sustaining Palliative Care Teams (PCTeams) as part of a randomized clinical trial to "Improve Palliative Care through Teamwork" (IMPACTT). Research Design and Methods: We conducted rapid ethnographic assessments of all NH ( N = 14) in the intervention arm. Data included semistructured interviews with direct care and administrative staff ( n = 41), field observations, and written materials. We used a phased approach to data analysis including open coding and comparative analyses within and across homes. Results: We found four key structural themes in our analysis including: administrative support, financial considerations, turnover and staffing, and competing priorities. The development and sustainability of the nascent PCTeams were constantly threatened by competing priorities and the key factor in their success was consistent and tangible administrative support. Discussion and Implications: While improving PC in NHs is a recognized priority, lack of stable infrastructure and unintended consequences of reimbursement policies created conditions which often thwarted the sustainability of the PCTeams.